2018
DOI: 10.1111/cid.12631
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic evaluation of natural teeth in anterior maxilla using the pink and white esthetic scores

Abstract: The average level of natural teeth in PES and WES assessment were around 13 and 9, respectively. The soft tissue margin, soft tissue contour and outline/volume of the crown were high-risk parameters for the esthetic outcomes of implant reconstructions. Underlying factors, such as age and gender, contributed to the esthetics of natural teeth change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
(100 reference statements)
0
15
0
1
Order By: Relevance
“…Any complications reported by the authors of the original article were included under the overall complications as efficacy outcome. Peri‐implant soft‐tissue esthetics was assessed clinically through the pink esthetic score (PES), 21 The PES ranges from 0 to 14 points, with the minimum clinically acceptable value ≥8 points 22,23 . Vertical bone resorption outcome was stratified into vertical buccal and vertical interproximal bone resorption.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Any complications reported by the authors of the original article were included under the overall complications as efficacy outcome. Peri‐implant soft‐tissue esthetics was assessed clinically through the pink esthetic score (PES), 21 The PES ranges from 0 to 14 points, with the minimum clinically acceptable value ≥8 points 22,23 . Vertical bone resorption outcome was stratified into vertical buccal and vertical interproximal bone resorption.…”
Section: Methodsmentioning
confidence: 99%
“…Peri‐implant soft‐tissue esthetics was assessed clinically through the pink esthetic score (PES), 21 The PES ranges from 0 to 14 points, with the minimum clinically acceptable value ≥8 points. 22 , 23 Vertical bone resorption outcome was stratified into vertical buccal and vertical interproximal bone resorption. Horizontal bone resorption outcome was stratified into horizontal buccal and overall horizontal bone resorption.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, soft tissue esthetic outcomes are of vital importance for achieving clinical esthetic success. The PES is an objective system for evaluating peri-implant soft tissues [15,41]. The system is based on seven variables-namely, mesial and distal papilla, the level of soft tissue margin, the contour, color, and texture of the soft tissue,as well as the alveolar process deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…This findings were similar to Loguercio et al (2015) (12) , as they reported no statistical significant difference in sensitivity between these two isolation methods after 1 week. This sensitivity may be as a result of gingival laceration, Pink esthetic score (PES) was found to be a suitable tool for reproducible evaluation of soft tissue around tooth structure Chen et al (2018) (5) and Fürhauser et al (2005) (8) . Analysis of PES regarding mesial papilla, distal papilla and alveolar process showed that both intervention groups scored 2 at each evaluation time.…”
Section: Loguercio Et Al (2015)mentioning
confidence: 99%